Fast Code Generation for Embedded Processors with Aliased Heterogeneous Registers - Ahn, Minwook; Paek, Yunheung (Transactions on High-Performance Embedded Architectures and Compilers II, 2009)
Many embedded processors have complex, irregular architectures resulting from the customization for the maximum performance and energy efficiency of target applications. One such example is the heterogeneous register architecture, which has fast, small-sized register files, for their specific uses, distributed over the data paths between different functional units. Although this architectural design may be good at achieving the H/W design goal of high speed, small area and low power, it requires highly expensive algorithms for optimal code generation. This is primarily because multiple registers contained in each file come with many different constraints subject to their design purposes, and often their names are aliased with each other; thus the final code quality is very sensitive to how properly such aliased, heterogeneous registers are utilized in every instruction. In this work, we propose a code generation approach to attack this complex problem. The experiments reveal that our approach is fast, practically running in polynomial time. In comparison with the related work, it achieves approximately 13% of code size reduction and 16% of speed increase.